2017
DOI: 10.1515/bmt-2016-0067
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the reliability of an inertial sensor-based gait analysis system

Abstract: Gait analysis is an important and useful part of the daily therapeutic routine. InvestiGAIT, an inertial sensor-based system, was developed for using in different research projects with a changing number and position of sensors and because commercial systems do not capture the motion of the upper body. The current study is designed to evaluate the reliability of InvestiGAIT consisting of four off-the-shelf inertial sensors and in-house capturing and analysis software. Besides the determination of standard gait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Several previous studies that measured joint angles using the inertial sensors showed good to excellent test-retest reliability, similar to our study. 19,20 These studies claimed that the motion of the upper body showed excellent ICC values with relatively small SEM and MDC values from the all three planes. These results indicate good relative and absolute reliability.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies that measured joint angles using the inertial sensors showed good to excellent test-retest reliability, similar to our study. 19,20 These studies claimed that the motion of the upper body showed excellent ICC values with relatively small SEM and MDC values from the all three planes. These results indicate good relative and absolute reliability.…”
Section: Discussionmentioning
confidence: 98%
“…Wearable inertial measurement units have increasingly been used in gait analysis applications with their validity or reliability usually assessed in healthy subjects [ 11 , 12 , 13 ]. Hamacher et al presented a mobile system exhibiting a high reliability, which was based on sensors attached to the forefeet [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gait analysis was performed with InvestiGAIT, an inertial sensor-based system consisting of four Shimmer3 sensors (Shimmer, Realtime Technologies Ltd, Dublin, Ireland) and an in-house Matlab program for recording and analyzing gait data. The basics of this sensor-based system, the calculation of the gait parameters and the measurement methods are detailed in Orlowski and Loose [23] and Orlowski et al [24].…”
Section: Gait Analysismentioning
confidence: 99%